Data processing chain for high spatial resolution magnetic survey: Application on the Neolithic site of le Pontet (Charente‐maritime, France). Issue 1 (9th November 2017) - Bruniaux, Guillaume; Mathé, Vivien; Lévêque, François; Camus, Adrien; Ard, Vincent
Abstract: This article focusses on an original magnetic survey protocol and its data processing chain. The use of a high sensitive magnetometer combined with a motorized total station permits production of a magnetic map with a high spatial resolution and a high precision of magnetic and positional measurements. The data processing enhances the final magnetic map by the removal and restoring the outlier values, measurement errors and magnetic disturbances. The magnetic survey was undertaken on the Neolithic site of Le Pontet at Saint‐Nazaire‐sur‐Charente (French Atlantic coast, between Bordeaux and La Rochelle). The site was chosen for geographical and archaeological characteristics such as its settlement period, the topography and the presence of different magnetic disturbances (proximity to roads and residential area). The data processing is mainly made on ungridded data and the gridding is the second to last step. The last step is to correct the relative height variation of the sensors between the prospecting lines (tracks) induced by the topography and operators. The use of a motorized total station allows accurate height determination of the sensors and an upward continuation is performed to correct the slight magnetic intensity variation induced by the relative height variation of the sensors. The results of the magnetic map bring out several causewayed enclosures, pits and postholes. This map will serve as a working basis for interdisciplinary studies and future archaeological studies of this site.